2012
DOI: 10.1177/000348941212100602
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of a Monolayer of Fibroblast Cells to Fibronectin under Sonic Vibrations in a Bioreactor

Abstract: Cells will adhere to a planar surface under stresses typical of phonation, which provide a more stringent test than adherence in a 3-dimensional matrix. The density of cell seeding on the coverslip played a role in cell-extracellular matrix adhesion, in that the cells adhered to each other more than to the fibronectin coating when the cells were nearly confluent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In vitro studies have shown that local vibrations and fluid agitation that generate shear stresses can influence the adhesion and proliferation of cells [45][46][47] . Above a specific oscillating stress limit, human fibroblasts fail to adhere to the substrate 45 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have shown that local vibrations and fluid agitation that generate shear stresses can influence the adhesion and proliferation of cells [45][46][47] . Above a specific oscillating stress limit, human fibroblasts fail to adhere to the substrate 45 .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that local vibrations and fluid agitation that generate shear stresses can influence the adhesion and proliferation of cells [45][46][47] . Above a specific oscillating stress limit, human fibroblasts fail to adhere to the substrate 45 . Additionally, in vitro studies have also shown that vibrations negatively influence the proliferation of certain types of mouse embryonic fibroblasts 46 , with vibration amplitudes measuring approximately 100 nm at frequencies of 100 Hz and 1 kHz being tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A device with the potential to satisfy these requirements is a custom-modified torsional rheometer-bioreactor (TRB). The TRB is a commercial rheometer (Gemini model, Malvern Instruments, LTD) with appliances to support tissue and cell viability [11][12][13]. Initial feasibility of the rheometer to deliver shear stresses at low audio frequencies with parallel plate appliances was shown by adjusting sample thickness, plate radius, material viscoelasticity, and motor inertia [11].…”
Section: Introductionmentioning
confidence: 99%
“…A third configuration, a glass coverslip mounted to the cup or the moving parallel plate of the TRB, delivered shear stresses up to 2200 Pa at 100 Hz to a monolayer of cells. This delivery was under controlled temperature, humidity, and CO 2 conditions using a custom incubator fitted to the commercial rheometer [13].…”
Section: Introductionmentioning
confidence: 99%